The fate of leachate of pharmaceuticals like amoxicillin, ibuprofen and caffeine in the soil using soil columns - Jodeh, Shehdeh; Staiti, Halimeh; Haddad, Marwan; Renno, Tamara; Zaid, Abdelnaser; Jaradat, Nidal; Kharoaf, Maher (European Journal of Chemistry, 2012)
From an environmental engineering point of view, pharmaceuticals such as antibiotics are a group of man-made chemicals of concern entering the environment in concentrations at which, the health effects are unknown. The problem that may be created by the presence of antibiotics at low concentrations in the environment is the development of antibiotic resistant microorganisms. In this study, three pharmaceutical drugs manufactured in Palestine were studied in waste water and their adsorption in agriculture soil was studied using soil columns. During the study of soil columns, it was noted that the concentration of caffeine in leachate was higher than that of ibuprofen and amoxicillin, as caffeine has higher aqueous solubility. Ibuprofen and amoxicillin were present in leachate with very small concentrations, due to their degradation and decomposition into other substances that may be harmful, and affect the natural properties of soil, groundwater and human health. The decomposition percentages of the pharmaceuticals in the soil columns were 97.82, 97.88 and 86.52% for amoxicillin, ibuprofen and caffeine for one year’s study, respectively. For the fifteen years, the decomposition percentages were 94.04, 96.60 and 93.70% for amoxicillin, ibuprofen and caffeine, respectively.